2011
DOI: 10.1088/0963-0252/20/3/034010
|View full text |Cite
|
Sign up to set email alerts
|

Observation of OH radicals produced by pulsed discharges on the surface of a liquid

Abstract: The hydroxyl radical (OH) plays an important role in plasma chemistry at atmospheric pressure. OH radicals have a higher oxidation potential compared with other oxidative species such as free radical O, atomic oxygen, hydroperoxyl radical (HO 2 ), hydrogen peroxide(H 2 O 2 ) and ozone. In this study, surface discharges on liquids (water and its solutions) were investigated experimentally. A pulsed streamer discharge was generated on the liquid surface using a point-to-plane electrode geometry. The primary gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
210
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 315 publications
(216 citation statements)
references
References 31 publications
6
210
0
Order By: Relevance
“…12,17,19 Underwater streamer discharges at positive polarity also have two propagation modes: a primary streamer and a secondary streamer. [20][21][22][23][24][25][26][27] The primary streamer appears at lower applied voltage with a propagation velocity of 2-3 km/s, having a semi-spherical brush-like structure ($500 lm) composed of many filaments. 22,26 All but a few filaments disappear within 400 ns, resulting in a tree-like structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12,17,19 Underwater streamer discharges at positive polarity also have two propagation modes: a primary streamer and a secondary streamer. [20][21][22][23][24][25][26][27] The primary streamer appears at lower applied voltage with a propagation velocity of 2-3 km/s, having a semi-spherical brush-like structure ($500 lm) composed of many filaments. 22,26 All but a few filaments disappear within 400 ns, resulting in a tree-like structure.…”
mentioning
confidence: 99%
“…23,24,26 Above a certain threshold voltage, the secondary streamer propagates with a velocity of greater than 10 km/s, for example, 25 reports, forming a filamentary structure of a few millimeters, dependent on gap distance. [20][21][22][23][24][25]27 In the case of low conductive water, secondary streamer propagation is followed by re-illuminations, which are restarts of the discharge in the formed gas channel, and show a dielectric-barrier discharge (DBD) like behavior with a stepwise propagation. 21,23,24 The secondary streamer and the re-illuminations are characterized by a continuous current with a duration of around 100 ns and subsequent spike currents.…”
mentioning
confidence: 99%
“…This mass transport may have occurred due to an electrohydrodynamic flow in liquid and a flow caused by an ionic wind generated above the liquid, which induces convection and diffusion in liquid. 25 In conclusion, we demonstrated the decomposition of salicylic acid to inorganic carbon using non-thermal atmospheric pressure plasma jet. Large amounts of OH radical were generated by plasma irradiation, and the radicals directly decomposed salicylic acid within 10 min.…”
Section: ¹1mentioning
confidence: 78%
“…Other researchers also show that the rate of OH radical formation varies from 10 −8 to 10 −10 M/s depending on plasma generation conditions. [44][45][46] It was observed that after 6-8 min of DBD operation, the intensity or concentration of 2-hydroxyterephthalic acid is reduced Fig. 4A, whereas the concentration of HTA is supposed to either increase or remain constant; it is to be noted that according to the reaction stoichiometry, the concentration of HTA is equivalent to the concentration of OH radicals.…”
Section: -mentioning
confidence: 99%